Government Subsidies and Enterprise Innovation: Evidence from China's Photovoltaic Industry - Cailou Jiang; Dehai Liu; Qin Zhu; Lu Wang (Discrete Dynamics in Nature and Society)
Government subsidies (GSs) have triggered a remarkable increase in the production capacity of photovoltaic (PV) electricity in China. However, the lack of core technologies has limited PV enterprises’ competitiveness in the global market. This research investigates the impacts of R&D subsidies and non-R&D subsidies on the innovation in PV enterprises. With samples of Chinese listed PV enterprises from 2010 to 2019, this study finds R&D subsidies exert a notable positive impact on the innovation in PV enterprises. In small and medium enterprises (SMEs) and enterprises without state-owned shares, both R&D subsidies and non-R&D subsidies have positive impacts on the innovation. Considering the policy orientation, R&D subsidies granted under demand-orientation policies promote the innovation in PV enterprises. The government should increase the amount of R&D subsidies, optimize the R&D subsidies’ evaluation mechanism, and reasonably grant R&D subsidies from the demand side.